(untitled) (Historia, 2021)
Heritage and collection are concepts that go hand-in-hand, as do collection and preservation. Similarly, preservation and access, while potentially in conflict, are partner concepts in the heritage context. It is the specific responsibility of South Africa’s heritage institutions to develop collections, to preserve such collections and to make these collections accessible. Useless if not accessible, heritage items hold both access to memory and the possibility of many untold histories. The manner in which our heritage is assembled into collections, researched, interpreted and presented has been subject to ongoing intellectual and political debate,1 particularly in terms of the impacts on community memory and identity. The manner, for example, in which South African museums address the issue of heritage has come increasingly under the spotlight in the last two decades, and whether initiatives and solutions have been successful is also currently under debate 2. History has always been fiercely contested terrain. Although the exact nature of the contest may have changed, the ferocity of battles around who gets to research, write and present accepted ordominant versions of history still remains